Multipacket reception in random access wireless networks fromsignal processing to optimal medium access control. - Tong, Lang
There has been considerable interest in the idea of cross-layer design of wireless networks. This is motivated by the need to provide a greater level of adaptivity to variations of wireless channels. This article examines one aspect of the interaction between the physical and medium access control layers. In particular, we consider the impact of signal processing techniques that enable multipacket reception on the throughput and design of random access protocols
Keywords: Cross-layer design; Multipacket reception; Optimal medium access control; Physical control layer; Random access protocols; Random access wireless networks; Signal processing; Throughput